2011
DOI: 10.1039/c0pp00284d
|View full text |Cite
|
Sign up to set email alerts
|

Cationic and radical intermediates in the acid photorelease from aryl sulfonates and phosphates

Abstract: The irradiation of a series of phenyl sulfonates and phosphates leads to the quantitative release of acidity with a reasonable quantum yield (≈0.2). Products characterization, ion chromatography analysis and potentiometric titration are consistent with the intervening of two different paths in this reaction, viz. cationic with phosphates and (mainly) radical with sulfonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 44 publications
(23 reference statements)
2
31
1
2
Order By: Relevance
“…[12,13] We (and others) have found that inorganic esters (phosphates, sulfonates), of general formula ArÀOZ, operate as nucleofugal leaving groups in the place of chlorides (path a in Scheme 1 b), [4,14] in competition with ArOÀZ bond cleavage (path b in Scheme 1 b). [15] The easy availability of such compounds makes the choice appealing, although the scope is little known. As a contribution to the clarification of the matter, we decided to carry out a systematic study of some esters of (trimethylsilylmethyl)phenols, more precisely, mesylates (1 a-c), triflates (2 a-c), and diethylphosphates (3 a-c; Figure 1), and to supplement product studies with a computational investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,13] We (and others) have found that inorganic esters (phosphates, sulfonates), of general formula ArÀOZ, operate as nucleofugal leaving groups in the place of chlorides (path a in Scheme 1 b), [4,14] in competition with ArOÀZ bond cleavage (path b in Scheme 1 b). [15] The easy availability of such compounds makes the choice appealing, although the scope is little known. As a contribution to the clarification of the matter, we decided to carry out a systematic study of some esters of (trimethylsilylmethyl)phenols, more precisely, mesylates (1 a-c), triflates (2 a-c), and diethylphosphates (3 a-c; Figure 1), and to supplement product studies with a computational investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Direct 4 b (27) 6 (6) 8 (4) Sens. [b] 4 b (tr) 6 (tr) 7'' (21), 7''' (15), 8 (51) 2 c Direct 4 c (8), 4'' (22) 6 (tr) Sens. [b] 6 (tr) 7'' (10), 7''' (15) 3 a Direct 7' (1), 7'' (9) Sens.…”
mentioning
confidence: 99%
“…[33] Fagnoni et al [34] schlugen vor,d ass elektronenrei-che Arylsulfonate wie Mesylat-und Tr iflatderivate bevorzugt durch eine heterolytische Spaltung der Ar-O-Bindung unter Freisetzung des entsprechenden Ar + -Kations und Sulfonat-Anions photolytisch zersetzt werden. Einer der akzeptierten Mechanismen der Säurebildung besteht in der homolytischen Photospaltung der Ar-O-Bindung.…”
Section: Arylsulfonatesterunclassified
“…Tatsächlich wird weit mehr Nebenprodukt durch eine Photo-Fries-Umlagerung erzeugt, die aus der Kombination von Radikalen zur Bildung von Hydroxyphenylsulfon-Derivaten besteht. [33] Fagnoni et al [34] schlugen vor,d ass elektronenrei-…”
Section: Arylsulfonatesterunclassified
“…43) The heterolytic cleavage of an O-aryl bond from T 1 to form a σ aryl cation is likely, as reported for OP esters that have an electron-rich aromatic group. 189) …”
Section: Thiono-thiolo Rearrangementmentioning
confidence: 99%